Antropologia fenomenologica e politica: Fine della democrazia? - Rezzonico, Paolo (Teologia, 2025)
The contribution stems from an analysis of the phenomenological insights of M. Merleau-Ponty and M. Richir regarding the transition from the purely anthropological moment to the intersubjective one first, and then to the political one. The categories taken into consideration are those of "institution" in opposition to any "constitutive" claim and of the "origin" of power. In this case, Richir's studies extend both to the ethnological field, through P. Clastres' research, and to the religious field through mythical-mythological accounts of the origin of power. The present work intends to show how, phenomenologically speaking, the limit of the manifestation of the phenomenon of the "political" indicates its meaning, in part indispensable - that same meaning which the democratic form and the Christian conception of power have always safeguarded and which, instead, in today's context, is dangerously endangered.